2017
DOI: 10.3390/ijerph14010097
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Japanese Cedar (Cryptomeria japonica) Wood Increases Salivary Dehydroepiandrosterone Sulfate Levels after Monotonous Work

Abstract: Employee problems arising from mental illnesses have steadily increased and become a serious social problem in recent years. Wood is a widely available plant material, and knowledge of the psychophysiological effects of inhalation of woody volatile compounds has grown considerably. In this study, we established an experimental method to evaluate the effects of Japanese cedar wood essential oil on subjects performing monotonous work. Two experiment conditions, one with and another without diffusion of the essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…However, the interaction between experimental time and conditions did not significantly change in all biomarker levels. We previously found that DHEA-s levels increase in response to the inhalation of volatiles derived from Japanese cedar wood (17). The difference between the results of our previous and present studies may be attributed to physiological differences among the participants in the present study.…”
Section: Analysis Of Subjective Assessmentscontrasting
confidence: 92%
See 4 more Smart Citations
“…However, the interaction between experimental time and conditions did not significantly change in all biomarker levels. We previously found that DHEA-s levels increase in response to the inhalation of volatiles derived from Japanese cedar wood (17). The difference between the results of our previous and present studies may be attributed to physiological differences among the participants in the present study.…”
Section: Analysis Of Subjective Assessmentscontrasting
confidence: 92%
“…Caffeine consumption on the day of the experiment was prohibited. An experimental room in our research institute (17) was used. The specification of the experimental room is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations